The Paradoxical Use of the Term Sulh: An Analytical Study from Quranic Perspective - Muhammad Rafiqul Hoque; Muhammad Mustaqim Mohd.Zarif (USIM Press, 2024)
Vol. 16 No. 1 (2020): Journal of Maʿālim al-Qurʾān wa al-Sunnah